Julián Ayuque: Narratividad y conflicto cultural - Plasencia Soto, Rommel (Nómadas. Critical Journal of Social and Juridical Science, 2013)
Article that reveals a writer expropriated and whose theme is the landscape and the history of the Huancavelica peoples. Trough the, you are tryng to trace of genealogy literary and establish a comparison the Andean call literature, tax of the memory and the oral tradition.